An examination of postharvest techniques to enable seafreight export of feijoa (Acca sellowiana [O.Berg.] Burret) : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Food Technology at Massey University, Manawatu Campus, Palmerston North, New Zealand - Oseko, Jacqueline Kwamboka (Massey University, 2020)
Export of feijoa (𝘈𝘤𝘤𝘢 𝘴𝘦𝘭𝘭𝘰𝘸𝘪𝘢𝘯𝘢 [O.Berg.] Burret) to the main markets in Europe, Asia and North America is currently by airfreight that is not only expensive but rather unsustainable as the industry expands. With the ongoing breeding works and expansions of plantings, growers will eventually have to seek for an economic mode of transport. As is the case with kiwifruit, apples, avocadoes, and squash, seafreight will provide an alternative option that is both cheaper and accommodates large fruit volumes. The short storage life of feijoa, however, is likely to pose a challenge to seafreight (that requires at least 6 weeks of storage) if appropriate postharvest techniques are not identified to extend storage life. Feijoa stores for about 4 weeks at 4 °C after which it becomes overripe, loses flavour, and develops chilling injury and internal browning. This study was undertaken to examine potential postharvest techniques that could extend storage life and maintain quality of feijoa. The postharvest techniques investigated were temperature and relative humidity management, harvest timing, step down conditioning, intermittent warming, chlorophyll fluorescence and development of non-destructive grading tools. The varieties used in this study were ‘Kakariki’, ‘Wiki Tu’ and ‘Triumph’ that were stored for 8 weeks under various conditions. To assess the effects of temperature and relative humidity in storage, ‘Kakariki’, ‘Wiki Tu’ and ‘Triumph’ were stored at 1 °C (85% RH) and 4 °C (88% RH). These conditions were set to result in equal water vapour pressure deficits at both temperatures. The effects of RH on feijoa quality during 8 weeks storage were tested by using a polyethylene liner (polyliner) to cover the fruit in each tray, for half of the treatments. Despite good retention of some attributes indicating quality (firmness and skin colour) for up to 8 weeks at 1 °C, many fruit developed chilling injury making it unsaleable and therefore causing huge losses. At both 4 °C and 1 °C the use of a polyliner resulted in reduced water loss, suggesting polyliners may be beneficial for feijoa storage. Given the chilling injury results, it is imperative to consider treatments that may reduce chilling injury and yet maintain fruit quality. To alleviate chilling injury and extend storage life of ‘Kakariki’, 2 harvesting times (early (H1) and commercial (H2)), 2 storage temperatures (2 °C and 4 °C) and three conditioning treatments (single step down, [6 d at 9 °C then moved to 2 °C or 4 °C ], double step down [3 d at 9 °C , 3 d at 6 °C then moved to 2 °C or 4 °C] and ‘no conditioning’ control [stored direct to 2 °C or 4 °C]) were established. Results showed that early harvested fruit had lower chilling injury incidence and retained more quality attributes thereby providing a possibility of extending Kakariki’ feijoa storage life. There was no evidence for a difference in quality arising from storage at 2 °C or 4 °C but it was evident that single or double step down conditioning simply allowed an extended period of postharvest ripening because of the 6 d delay in reaching the more appropriate storage temperature of 2 °C or 4 °C. This led to faster deterioration of fruit. Therefore, it is advisable to rapidly cool feijoa soon after harvest to reduce metabolism and ripening; but then sell the fruit before they develop CI. To assess the effects of intermittent warming (IW) on improving quality of ‘Triumph’ fruit. Three (3) intermittent warming conditions were tested (IW from 4 °C to 20 °C for 1 d after every 6 d storage, IW from 4 °C to 20 °C for 1 d after every 10 d storage and control) and stored at 4 °C for 6 weeks. Chlorophyll fluorescence was used as a non-destructive tool to assess quality. The results showed that intermittent warming just like conditioning treatments, accelerated ripening leading to faster deterioration. A decline in quantum yield (𝘍𝘷/𝘍𝘮) was observed during storage in the absence of CI. This suggests that it is linked to loss of chlorophyll content and chloroplast membrane injury associated with photosystem II (PSII) as feijoa ripened. The continuous decline in quantum yield (𝘍𝘷/𝘍𝘮) offers potential for a non-destructive technique to assess feijoa ripeness and could therefore be used in a cool store to detect batches of fruit that are ripening more quickly for immediate sales or those ripening slowly that may be more suited to export or long storage. To re-evaluate the internal maturity/ripeness scale developed by scanned images of ‘Kakariki’, ‘Wiki Tu’ and ‘Triumph’ varieties from at harvest through storage were assessed against the PFR scale. The results showed that the PFR scale worked well for maturity assessment of ‘Kakariki’, ‘Wiki Tu’ and ‘Triumph’ varieties at harvest, despite their quite different internal anatomy. The same scale was also appropriate for each variety as a post-storage ripeness indicator. Evidence also suggested that one new step was required an internal maturity rating of 1.5. The problem was that fruit at stage 1 could be immature (and not ripen during storage) or mature. This new stage was used to describe fruit showing the first signs of locular gel clearing, suggesting that ripening was definitely underway. Firmness (non-destructively assessed) at harvest was correlated with quality after storage and therefore showed potential to predict fruit ripening behaviour in storage. This implies, that firmness could be used non-destructively in sorting lines to select firm fruit for long storage or soft fruit for immediate consumption. Based on these findings’, storage life of ‘Kakariki’, ‘Wiki Tu’ and ‘Triumph’ feijoa could not be reliably extended beyond 4 to 6 weeks and therefore seafreight export is still risky. The wide range of maturity variation within any batch of harvested feijoas accounts for much of this risk. Future research should focus on finding a rapid, non-destructive technique that can detect the new internal maturity/ripeness rating 1.5. This would assist growers to grade early harvested fruit and select mature but longer-storing fruit for export.
Keywords: Feijoa; Postharvest technology; Transportation; New Zealand; 300604 Food packaging, preservation and processing